Regulating Shaker Kv channel clustering by hetero-oligomerization - Nsasra, Esraa; Peretz, Guy; Orr, Irit; Yifrach, Ofer (Frontiers in Molecular Biosciences, 2023)
Scaffold protein-mediated voltage-dependent ion channel clustering at unique membrane sites, such as nodes of Ranvier or the post-synaptic density plays an important role in determining action potential properties and information coding. Yet, the mechanism(s) by which scaffold protein-ion channel interactions lead to channel clustering and how cluster ion channel density is regulated are mostly unknown. This molecular-cellular gap in understanding channel clustering can be bridged in the case of the prototypical Shaker voltage-activated potassium channel (Kv), as the mechanism underlying the interaction of this channel with its PSD-95 scaffold protein partner is known. According to this mechanism, changes in the length of the intrinsically disordered channel C-terminal chain, brought about by alternative splicing to yield the short A and long B chain subunit variants, dictate affinity to PSD-95 and further controls cluster homo-tetrameric Kv channel density. These results raise the hypothesis that heteromeric subunit assembly serves as a means to regulate Kv channel clustering. Since both clustering variants are expressed in similar fly tissues, it is reasonable to assume that hetero-tetrameric channels carrying different numbers of high- (A) and low-affinity (B) subunits could assemble, thereby giving rise to distinct cluster Kv channel densities. Here, we tested this hypothesis using high-resolution microscopy, combined with quantitative clustering analysis. Our results reveal that the A and B clustering variants can indeed assemble to form heteromeric channels and that controlling the number of the high-affinity A subunits within the hetero-oligomer modulates cluster Kv channel density. The implications of these findings for electrical signaling are discussed.